Implementation of Problem-Based Learning to Develop Students Creative Thinking Ability - Utomo, Budi (Journal of Education Method and Learning Strategy, 2023)
This study aims to describe the application of problem-based learning to develop the creative thinking skills of PGSD. One of the advantages of the problem-based learning model is being able to train students in using the various concepts, principles, and skills they have learned to solve the problems they are facing. With the application of problem-based learning, the ability to think creatively can develop, because the creative thinking skills observed in this study are in the form of the ability to identify, analyze, solve problems, think logically, and make decisions correctly. Because the results of the verification process show that it is significant. There are many types of creative thinking-based learning models used to address educational problems, but one of the most effective is the problem-based learning model, which requires each child to have a unique set of beliefs and values. Complement one another, enabling teachers to think creatively for each student as they tackle a given problem.